Exploring Effects of Age on Conflict Processing in the Light of Practice in a Large-Scale Dataset. - Reiber, Fabiola; Ulrich, Rolf (Experimental Aging Research)
The possible decline of cognitive functions with age has been in the focus of cognitive research in the last decades. The present study investigated effects of aging on conflict processing in a big dataset of a Stroop-inspired online training task. We focused on the temporal dynamics of conflict processing in the light of task practice by means of inspecting delta plots and Lorenz-interference curves to gain insights on a process level. The results indicate a relatively constant increase of cognitive conflict over the course of adulthood and a decrease with practice. Furthermore, the latency of the automatic processing of conflicting information relative to the controlled processing of task-relevant information decreases relatively constantly with age. This effect is moderated by practice, that is, the relative latency of the automatic processing decreases less with age at high practice levels. As such, practice seems to be able to partially counteract age-related differences in conflict processing, on a process level.